2000
DOI: 10.1038/sj.jp.7200416
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Pneumonia: Comparison of 4 vs 7 Days of Antibiotic Therapy in Term and Near-Term Infants

Abstract: Four days of antibiotic therapy plus a 24-hour period of observation for selected cases of neonatal pneumonia appears to be comparable to 7 days of therapy. It is important to note that newborns in our institution receive a single dose of penicillin soon after birth as part of our group B streptococcal sepsis prophylaxis program, and all infants in this study received prophylaxis prior to the onset of respiratory symptoms. Furthermore, only infants who were asymptomatic after 48 hours of antibiotic therapy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 7 publications
(10 reference statements)
3
26
0
Order By: Relevance
“…These studies either documented no patients with bacteremia [30,31] or did not report on this subgroup [32-34]. …”
Section: Resultsmentioning
confidence: 99%
“…These studies either documented no patients with bacteremia [30,31] or did not report on this subgroup [32-34]. …”
Section: Resultsmentioning
confidence: 99%
“…5 Jackson et al demonstrated that stable newborns with gestational age of at least 35 weeks and birth weight of at least 2,100 g, not requiring cardiorespiratory monitoring or respiratory support, could be admitted for intramuscular antibiotic treatment and monitoring to the normal newborn nursery and do not necessarily require transfer to a more intensive level of care. 18,[32][33][34] Neonatal antibiotics regime should be narrowed to target the specific pathogen once identified and should be discontinued when results of work-up for neonatal sepsis (e.g., negative C-reactive protein and/or serial blood cell counts) become available in culture negative neonates.…”
Section: Discussionmentioning
confidence: 99%
“…In the chapter on bacterial sepsis and meningitis, Klein recommend 10 days of therapy for culture-proven sepsis with minimal or absent focal infection [22]. However, there is a paucity of RCTs evaluating the rationale and safety of the appropriate duration of therapy [5355]. Table 2 describes the RCTs evaluating shorter versus longer courses of antibiotic therapy in neonatal pneumonia and culture-proven sepsis.…”
Section: Duration Of Antimicrobial Therapy For Proven Bacterial Sementioning
confidence: 99%
“…Engle et al [53] randomized cases of neonatal pneumonia to either 4-day or 7-day course of antibiotics. Randomization was done on day 4 of antibiotic therapy if the infants were completely asymptomatic for at least 48 hours.…”
Section: Duration Of Antimicrobial Therapy For Proven Bacterial Sementioning
confidence: 99%